Thermal performance of FAU Maranhao building in two historic moments - Neves, Letícia de Oliveira (Universidade Estadual de Campinas, 2016)
The FAU Maranhao building, beyond being an important architectural heritage of Sao Paulo city, is recognized for providing good environmental quality to its occupants. Since the building has already housed distinct uses, this paper presents studies that point out the thermal response of the building to the climate in which it is located, in two historical moments: right after its construction, which had a residential use, and nowadays, which has an educational use. To that end, thermal performance and thermal discomfort probability analyses were performed for selected rooms, through experimental research based on computer simulations using EnergyPlus software. Results indicate a good contribution of the construction’s high thermal mass on reducing the indoor temperature fluctuation and a low occurrence of thermal discomfort periods, demonstrating the building’s suitability to modifications on its pattern of use occurred during its history. In the educational use the air change rates obtained per natural ventilation, however, were lower than the residential use, affecting the healthiness of users due to higher occupancy rate. A qualitative approach of the results enabled to highlight important thermal performance issues and singularities about the resiliency of historic buildings that changes its use over time.